2018
DOI: 10.1186/s12883-018-1013-8
|View full text |Cite
|
Sign up to set email alerts
|

Glutathione S-transferase M1 and T1 polymorphisms and the risk of mild hepatotoxicity induced by carbamazepine in a tunisian population study

Abstract: BackgroundThe aim of this study was to evaluate whether the glutathione S-transferase M1 (GSTM1) and T1 (GSTT1) null alleles may contribute to carbamazepine-induced hepatotoxicity.MethodsA cross-sectional prospective study was conducted to identify the frequency distribution of GSTM1 and GSTT1 alleles in 129 Tunisian epileptic patients treated with carbamazepine. Null alleles were determined using a Polymerase Chain Reaction. Serum alanine aminotransferase (ALT) and aspartate aminotransferase (AST) were measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…Among the top ten inter-donor variable genes (ICC: 58–89%, Fig. 2g ), XIST, ZNF705D, GTF2IRD2, and USP32P2 have differential expression between ovary and prostate/testis; RHD encodes a key protein in the Rh blood group system; and GSTM1 belongs to a highly polymorphic supergene family and affects heterogeneous response to toxicity 25 . These genes appeared to capture more diverse types of differences among donors than their counterparts from scRNA-seq data.…”
Section: Resultsmentioning
confidence: 99%
“…Among the top ten inter-donor variable genes (ICC: 58–89%, Fig. 2g ), XIST, ZNF705D, GTF2IRD2, and USP32P2 have differential expression between ovary and prostate/testis; RHD encodes a key protein in the Rh blood group system; and GSTM1 belongs to a highly polymorphic supergene family and affects heterogeneous response to toxicity 25 . These genes appeared to capture more diverse types of differences among donors than their counterparts from scRNA-seq data.…”
Section: Resultsmentioning
confidence: 99%
“…The presence of two null alleles of the GSTM1 gene leads to the absence of the protein product of this gene, which contributes to the development of oxidative stress, causes an increase in the level of DNA adducts and can provoke the development of various liver pathologies. 11,12 A number of research findings show its important prognostic significance in the development of occupational diseases. 13,14 In contrast to these results, our study showed that there was no significant difference in the distribution of the GSTM1 gene genotypes among workers depending on the presence or absence of occupational pathology.…”
Section: Discussionmentioning
confidence: 99%
“…Both glutathione S-transferase class M1 (GSTM1) and class T1 (GSTT1) are involved in conjugation reactions of the main metabolite and also in the detoxification of toxic metabolites of CBZ ( Bu et al, 2005 ). Findings in 129 Tunisian epileptic patients treated with CBZ suggest that the GSTM1 (-) allele may be considered as a risk factor for CBZ-induced hepatotoxicity ( Chbili et al, 2018 ). Japanese researchers observed a link between the lack of GSTM1 and increased levels of hepatic enzymes in 192 patients treated with CBZ and in 149 patients treated with valproate sodium ( Ueda et al, 2007 ; Fukushima et al, 2008 ).…”
Section: Pharmacogenetics Of Important Drugs Used In Migraine Tension...mentioning
confidence: 99%